The Structural Changes in the Use of Present Indefinite Tense Among Dani, Lani, And Yali Language Speakers - Halitopo, Manase H; Kogoya, Napius; Maitimu, Laura Sansa (Universitas Kapuas, 2025)
The Indonesian Island of Irian Jaya, home to the Papuan people, is distinguished by its extensive linguistic diversity, featuring more than 300 indigenous languages, such as Dani, Lani, and Yali. This study examines the structural changes in these languages, specifically regarding their use of the Simple Present Tense. The study aims to investigate the function of grammatical structures in Dani, Lani, and Yali and to understand the implications of these changes for the respective linguistic communities. The study employed a rigorous methodology involving observations, interviews, and recording sessions with tribal leaders and key community stakeholders to systematically gather data from the relevant language groups. The findings provide substantial insights into the grammatical alterations in these languages, enhancing understanding of the linguistic dynamics in Papua. This research aids in preserving linguistic heritage and enhances educational methodologies on the island. This work highlights the importance of preserving Papua's distinctive linguistic diversity and enhancing our understanding of its complex grammatical transformations through the documentation and analysis of these under-researched languages.